ANALISIS PENGARUH ARUS KAS DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - cintiya; Poniman (SCIENTIA JOURNAL, 2022)
This study aims to analyze the effect of cash flow and accounting profit on stock returns of manufacturing companies listed on the Indonesia Stock Exchange. The variables studied in this study are operating cash flow, investment cash flow, funding cash flow and accounting profit as independent variables, while stock returns as the dependent variable. In this study, the methods used for data analysis were descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis testing by processing the SPSS (Statistical Product and Service Solutions) version 26 program. The data used in this study were secondary data. namely the company's annual financial statements used in the research sample. The research sample is 6 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period which were taken using the purposive sampling method. The results of this study based on the T-test showed that operating cash flow had an effect on stock returns with a t-count value of -2.166 > 2.056 (t-table) and a significance level of 0.040 <0.05, investment cash flow had no effect on stock returns with a value of t-count is 0.169 > 2.056 (t-table) and a significance level of 0.867 > 0.05, funding cash flow has an effect on stock returns with a t-count value of -3.912 > 2.056 (t-table) and a significance level of 0.001 < 0, 05 and accounting earnings have an effect on stock returns with a t-count value of 5.234 > 2.056 (t-table) and a significance level of 0.000 <0.05. Based on the results of the F test, the results are 12.299 (F-count) > 2.759 (F-table) and a significance value of 0.000 <0.005 so that operating cash flow, investment cash flow, funding cash flow, and accounting profit significantly affect return share.